1998
DOI: 10.1016/s0014-5793(98)00751-0
|View full text |Cite
|
Sign up to set email alerts
|

CH domains revisited

Abstract: A sequence motif of about 100 amino acids, termed the`calponin homology domain' has been suggested to confer actin binding to a variety of cytoskeletal and signalling molecules. Here we analyse and compare the sequences of all calponin homology domain-containing proteins identified to date. We propose that single calponin homology domains do not confer actin-binding per se and that the actin-binding motifs of crosslinking proteins, which comprise two disparate calponin homology domains, represent a unique prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
95
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 120 publications
(97 citation statements)
references
References 20 publications
2
95
0
Order By: Relevance
“…35). It is, however, worth noting that the C. elegans genome contains proteins closely related to the SM22-like members of the CaP family (consisting of a single copy of both a CLIK-23 repeat and a single N-terminal calponin homology domain) but also Vav and IQGAP-like proteins harboring a single calponin homology domain (8,9) and no CLIK-23 module. Thus, UNC-87 may be a CaP ortholog specialized for actin filament assembly processes in invertebrate obliquely striated muscle.…”
Section: Unc-87 Is An Actin-bundling Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…35). It is, however, worth noting that the C. elegans genome contains proteins closely related to the SM22-like members of the CaP family (consisting of a single copy of both a CLIK-23 repeat and a single N-terminal calponin homology domain) but also Vav and IQGAP-like proteins harboring a single calponin homology domain (8,9) and no CLIK-23 module. Thus, UNC-87 may be a CaP ortholog specialized for actin filament assembly processes in invertebrate obliquely striated muscle.…”
Section: Unc-87 Is An Actin-bundling Proteinmentioning
confidence: 99%
“…We have shown recently that a unique sequence motif found in the C-terminal third of the calponin (CaP) 1 molecule and other members of the CaP family of actin-associated proteins (9), namely a 23-amino acid residue repeat, which we will refer to from now on as the CLIK-23 repeat, forms an independent actin-binding site (10). This finding was corroborated by Mino et al (11) who demonstrated the direct interaction of a peptide corresponding to the first CaP repeat with actin in vitro.…”
mentioning
confidence: 99%
“…Proteins containing the CH domain are categorized into three groups: (1) the fimbrin family of monometric actincross linking molecules which contain two actinbinding domains; (2) diametric cross linking proteins and monometric F-actin binding proteins each of which contains one actin-binding domain, and (3) proteins containing a single amino-terminal CH domain (Stradal et al, 1998). According to the categorization indicated above, HELAD1 is classified into the third group that includes calponin, a molecule involved in contraction of smooth muscle, IQGAP, a signaling molecule, and the proto-oncogene Vav.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, both calponin and a -actinin contain one or two calponin homology domains (CH domains) that, at least in the case of a -actinin, are directly involved in the binding of these ABPs to actin (7,17). Therefore, we would expect mutual exclusion of these ABPs from actin laments.…”
Section: Discussionmentioning
confidence: 99%